Analisis Kelayakan Investasi Penggantian Truck Box dengan Metode IRR, NPV, dan PP - Vikaliana, Resista; Iskandar, Yelita Anggiane; Ramadhan, Muhammad Raihan; Sembiring, Ellease Davira Christy; Hawari, Farisan; Zein, Ghalda Ghaliyah; Ramandy, Johan Almer; Asif, St Nurauliyah Nasri (Universitas Mercu Buana, 2023)
In making an investment, it is necessary to carry out an investment feasibility test to assess the feasibility of the investment plan to be carried out. This study aims to examine the investment feasibility of replacing truck boxes with a larger capacity for distribution transportation at CV Jaya Proteindo. In the case of CV Jaya Proteindo, the method used to test the feasibility of investing in replacing a vehicle whose economic life is almost exhausted is using the Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period (PP) methods as well as the calculation of benefits or profits. in distribution using the vehicle to be invested. Based on the results of the research conducted, the replacement of vehicles at CV Jaya Proteindo using either 2 Mitsubishi L300 units or 1 Mitsubishi FE 74S unit was declared feasible, because it provided results that met the eligibility criteria of the methods tested.. Both types of vehicles generate an NPV value of ≥ 0, a short Payback Period or 2 months, and an IRR greater than the interest rate of 4.75%. Then a calculation of the benefits or advantages of both types of vehicles is carried out and it is obtained that the Mitsubishi FE 74S has a higher annual cash flow and lower annual distribution costs. Therefore, it is concluded that the investment solution in CV Jaya Proteindo is the replacement of distribution vehicles using 1 unit of Mitsubishi FE 74S which is declared feasible and more financially profitable with a greater cash flow of Rp82,445,000.00 per year and smaller distribution costs of Rp31,548,854.17 per year when compared to the use of 2 units of Mitsubishi L300.